Pencegahan Perilaku Bullying Melalui Pembelajaran PPKn Pada SMKN - Bakhtiar, Dr. Bakhtiar; Gani, Andika Wahyudi; Nur Rahmayanti, Siti (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2023)
Abstract: This study aims to find out, (1) The form of bullying behavior in students at SMKN 3 Takalar, (2) Strategies for preventing bullying behavior through PPKn learning for students at SMKN 3 Takalar (3) The factors that influence strategies for preventing bullying behavior through Civics learning in SMKN 3 Takalar students. Data collection techniques through observation, interviews and documentation. Data obtained from interviews with 3 PPKn teachers, 1 student teacher and 3 students. Checking the validity of the data using data source triangulation techniques. The results showed that; (1) forms of bullying behavior that occur at SMKN 3 Takalar in the form of verbal bullying, rational bullying, and physical bullying; (2) strategies for preventing bullying behavior carried out by PPKn teachers, namely by providing enlightenment to students that bullying behavior is bad behavior, implementing rule boards, providing guidance through Civics learning materials that include the cultivation of noble character values and moral values. as well as fostering and guiding students to be better; (3) the supporting factor for the implementation of the first bullying behavior prevention is the role of civics educations teachers in instilling positive moral values through learning materials in class, cooperation with school residents such as if a teacher finds students bullying their friends, they will be immediately punished. Report to BK for advice and guidance regarding bullying behavior that should not be done. As well as awareness of school residents, especially students, to apply the positive value that have been taught in their daily lives. the inhibiting factor in preventing bullying behavior is that it has become a habit, also because of family factors and the assumption that this bullying behavior is just a joke without them knowing what impact it can have on victims of bullying.